The Non-Contiguous Allocation Strategies Performance for k-ary n-cube Connected Multi Computers Using Smallest Job First Scheduling Strategy - Muhammed Ahmed Awaad Al-Kerboly, Doreyed (International Journal of Psychosocial Rehabilitation, 2020)
The performance of the famous non-contiguous allocation algorithms (Paging (0), Multiple Partner, and Random) proposed for k-ary n-cube connected multi-computers has been compared by wide simulation experiments. In the paper, the smallest job first scheduling strategy (SJF) and three communication patterns were measured; these are random, one-to-all, and all-to-all. The simulation results display that the performance of non-contiguous paging (0) is superior to that of wholly additional non-contiguous allocation algorithms (strategies) in our scenario due to their capability to reduce together (internal and external) fragmentation and reduce the dispute inside the network by preserving a huge contiguity degree through allocated processors.